DEVIATION ROTOR GYROCOMPASS MOVABLE BASIS - Левчук, Катерина Григорівна; Цідило, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
There is obtained a mathematical model gyrocompass on the moving basis. Nonlinear differential equations integrated of the method successive approximations Picard-Peano. The dynamics gyrocompass investigated to the second approximation. Gyrocompass deviation from the desired position obtained averaging.